Catalogue of the Egyptian Ephydroidea (Diptera: Schizophora: Acalyptratae) - El-Hawagry, Magdi S.; Zatwarnicki, Tadeusz; Ebrahim, Ayman M. (Zootaxa, 2018)
We present a catalogue of all known taxa of the superfamily Ephydroidea in Egypt. Old World synonymies, type localities, type depositories, world distributions by biogeographic realm(s) and country, Egyptian localities and dates of collection are provided. A total number of 117 species belonging to 45 genera, 18 tribes, 7 subfamilies, and representing 3 families has been catalogued. The treated families are: Ephydridae (shore flies or brine flies), Drosophilidae (vinegar flies or fruit flies) and Braulidae (bee lice). One shore fly species, Psilopa clara (Wollaston, 1858), is recorded for the first time from Egypt. Two new synonyms of shore flies are proposed, namely: Philotelma ulianai Raffone, 2011 = Ephydra (Ephydra) macellaria Egger, 1862 and Notiphila rufitarsis Macquart, 1851 = Allotrichoma biroi Cresson, 1929. Lectotypes are designated for three shore fly species, namely: Psilopa pectinata Hendel, 1931; Rhynchopsilopa nitidissima Hendel, 1931 and Notiphila rufitarsis Macquart, 1851.